High Court of New Zealand and Tokelau – A Recent Case - Angelo, AH; Allan, Ashleigh (Victoria University of Wellington Law Review, 2012)
The decision of the High Court of New Zealand in the case of Pisaina Leilua-Lei Sam v The Council for the Ongoing Government of Tokelau and Faipule Foua Toloa (Sam v COG) provides an opportunity to consider the court system of Tokelau and to glimpse a largely unknown area of the law of New Zealand. It appears that Sam v COG is the first case to be decided by the High Court of New Zealand in the exercise of its jurisdiction as a separate Court of justice for Tokelau. This case note deals in turn with the structure of Tokelau's court system, the judgment in Sam v COG, and the future of the system.